Acupressure the PC6 point for alleviating postoperative nausea and vomiting: A systematic review protocol. Issue 33 (August 2019) - Yang, Jiao; Jiang, Yilu; Chen, Ying; Sun, Mingsheng; Chen, Jiao; Zheng, QianHua; Liang, Fan-rong
Abstract: Background: Postoperative nausea and vomiting (PONV) are common complications following surgery and anesthesia, conventional drugs can carry some side effect in treating PONV. Acupressure PC6 point has been widely used in clinical, but there still exist controversy towards its effectiveness and safety. We, therefore, design this study to systematically assess the effectiveness and safety of acupressure PC6 point for treating PONV. Methods and analysis: Nine online databases will be searched from their inception to May 2019. We will include randomized controlled trials (RCTs) involving patients with PONV and receiving acupressure PC6 point treatment. Two independent reviewers will be responsible for the selection of studies, data extraction and risk of bias assessment. RevMan V.5.3 software will be used for data synthesis with either a fixed effects model or random effects model depending on the heterogeneity test. Evidence quality will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation system (GRADE). The primary outcome is incidence of postoperative nausea (PON), postoperative vomiting (POV) and PONV events during 0 to 6 hours and after 6 hours of the treatment. The secondary outcome is the number of people who use emergency drugs and the number of people with adverse reactions. A meta-analysis will be conducted if no considerable heterogeneity is detected. The results will be presented as risk ratios with 95% confidence interval (CIs) for dichotomous data and weighted mean differences or standardized mean differences with 95% CIs for continuous data. Results: This study will provide a high-quality evidence to assess the effectiveness and safety of acupressure PC6 point for patient with PONV. Conclusion: This review will provide up-date evidence of whether acupressure of PC6 point is an effective and safe intervention for PONV. PROSPERO registration number: CRD42019135598